2015
DOI: 10.3171/2015.3.peds1553
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric skull fracture diagnosis: should 3D CT reconstructions be added as routine imaging?

Abstract: OBJECT The authors compared the efficacy of combining 2D+3D CT reconstructions with standard 2D CT images in the diagnosis of linear skull fractures in children with head trauma. METHODS This was a retrospective evaluation of consecutive head CT studies of children presenting with head trauma. Two experienced pediatric neuroradiologists in consensus created the standard of reference. Three readers indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 17 publications
1
51
0
2
Order By: Relevance
“…In a recent report, 2D+3D computed tomography (CT) in combination were shown to have high sensitivity in the diagnosis of linear skull fractures in all children and increased specificity in children less than 2 years of age, with concurrent intracranial lesions being detected in 15%–30% of these cases. 12) Hospitalization is not necessary for many children with non-displaced skull fractures but patients with mental status changes, additional injuries, or those suspected to be cases of AHT may require hospitalization. 13) …”
Section: Primary Tbimentioning
confidence: 99%
“…In a recent report, 2D+3D computed tomography (CT) in combination were shown to have high sensitivity in the diagnosis of linear skull fractures in all children and increased specificity in children less than 2 years of age, with concurrent intracranial lesions being detected in 15%–30% of these cases. 12) Hospitalization is not necessary for many children with non-displaced skull fractures but patients with mental status changes, additional injuries, or those suspected to be cases of AHT may require hospitalization. 13) …”
Section: Primary Tbimentioning
confidence: 99%
“…In routine clinical practice, head computerized tomography (CT) is a sensitive measure to diagnose post-traumatic skull fractures (7). In some circumstances, two dimensional (2-D) CT images cannot be sufficient to demonstrate subtle or linear fractures in the axial plane on images (8). Skull fractures may occur in linear, depressed, diastatic, or basilar (skull base) fashion, and linear fractures constitute approximately 75% of all fractures (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In some circumstances, two dimensional (2-D) CT images cannot be sufficient to demonstrate subtle or linear fractures in the axial plane on images (8). Skull fractures may occur in linear, depressed, diastatic, or basilar (skull base) fashion, and linear fractures constitute approximately 75% of all fractures (7,8). Intracranial injury is a significant cause of mortality and morbidity in children (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orman et al . retrospectively evaluated consecutive head CT of pediatric head trauma and concluded that the combination of 2‐D and 3‐D CT had higher sensitivity in the diagnosis of all pediatric linear skull fractures and increased specificity in children <2 years old . Approximately 75% of all skull fractures are linear fractures .…”
mentioning
confidence: 99%